2019
DOI: 10.1002/jbt.22403
|View full text |Cite
|
Sign up to set email alerts
|

A ginger derivative, zingerone—a phenolic compound—induces ROS‐mediated apoptosis in colon cancer cells (HCT‐116)

Abstract: Zingerone (ZO), an active phenolic agent derived from Zingiber officinale (Ginger), has many pharmacological properties such as antioxidant, antiangiogenic, and antitumor. However, its potential value in cancer and the mechanism by which ZO wields its therapeutic effects remain obscure. Therefore, in this current study, we explored the effects of ZO on suppressing cell proliferation and enhancing apoptosis in colon cancer cells (HCT116). Our results indicated that ZO significantly enhances the production of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 42 publications
(36 reference statements)
0
30
0
Order By: Relevance
“…6-Shogaol has been demonstrated to have potential anticancer activities towards human renal-cell carcinoma 786-O [ 76 ] and ovarian cancer cell lines A2780 [ 77 ], and head and neck squamous cell carcinoma cell lines [ 78 ]. Studies showed that 6-shogaol had a dose-dependent antiproliferative effect and induced the apoptosis of head and neck squamous cell carcinoma cell lines by downregulating survivin [ 78 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6-Shogaol has been demonstrated to have potential anticancer activities towards human renal-cell carcinoma 786-O [ 76 ] and ovarian cancer cell lines A2780 [ 77 ], and head and neck squamous cell carcinoma cell lines [ 78 ]. Studies showed that 6-shogaol had a dose-dependent antiproliferative effect and induced the apoptosis of head and neck squamous cell carcinoma cell lines by downregulating survivin [ 78 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Studies showed that 6-shogaol had a dose-dependent antiproliferative effect and induced the apoptosis of head and neck squamous cell carcinoma cell lines by downregulating survivin [ 78 ]. 6-Gingerol inhibited STAT-3 translocation of ovarian cancer cells to inhibit cell proliferation and induce apoptosis [ 77 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…A wide variety of pre-polymerised polymethyl methacrylate (PMMA) blocks have been introduced on the market based on further studies related with nanoparticles and data was produced on surface roughness [11]. Our team has extensive knowledge and research experience that has translated into high quality publications [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Open Accessmentioning
confidence: 99%
“…The eff ects of zingerone on suppressing cell proliferation and enhancing apoptosis in colon cancer cells (HCT116) was explored by Su, et al [30]. The results indicated that zingerone signifi cantly enhances the production of reactive oxygen species, lipid peroxidation (Thiobarbituric Acid Reactive Substance [TBARS]), and loss of cell viability; and reduces mitochondrial membrane potential and antioxidant levels (SOD, CAT, and GSH) in ZO-treated HCT116 cells in a dose-dependent (2.5, 5, and 10 μM) manner.…”
Section: Colon Cancermentioning
confidence: 99%